Implementasi Kebijakan Pendidikan Inklusif : Studi Kasus SMP Negeri 15 Tanjungpinang - Elda Lahesti; Edy Akhyary; Agus Hendrayady (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Inclusive Education is a way to equip children without separation, all of whom deserve a good education. The facts that researchers get in implementing inclusive education policies are the lack of supporting facilities and infrastructure and a lack of teaching staff. This study aims to determine the Implementation of Inclusive Education Policy: Case Study SMP NEGERI 15 TANJUNGPINANG. The method used in this research is qualitative research using two sources of data, namely primary data and secondary data. This study uses policy implementation indicators from Merilee S. Grindle's theory with two indicators, namely policy content and policy environment. The contents of the policy consist of: 1) Affected interest, which is in its interests, namely 12 years of compulsory education and inclusive education goals, 2) Type Of Benefits, the benefits obtained are equal opportunities between children with special needs and their peers, 3) Site Of Decision Making, for the degree of change it is expected that children with special needs have space to mingle with their peers and the community, 4) Site Of Decision Making, TANJUNGPINANG 15 NEGERI Middle School has a shortage of educators to implement inclusive education to the fullest, 5) Program Implementors, program implementers coordinate with each other with related agencies, 6) Resources committed, resources in implementing this policy have a shortage of funds and educators. While the policy environment consists of: 1) Power, Interests, And Strategic Of Actors Innovative, socialization carried out to introduce inclusive education through the media, 2) Institutional And Regime Characteristics, public understanding of inclusive education policies has misunderstandings, 3) Compliance and Responsiveness, This indicator goes according to the ability of the executor and there are deficiencies. From the research results, the success of implementing inclusive education policies is still not optimal even though the benefits of inclusive education policies can be felt by children with special needs so that they can feel competitive with their peers.